Biofilm Formation of Pseudomonas aeruginosa in Cystic Fibrosis: Mechanisms of Persistence, Adaptation, and Pathogenesis - Dayana Borisova; Tsvetelina Paunova-Krasteva; Tanya Strateva; Stoyanka Stoitsova (Microorganisms, 2025)
Cystic fibrosis (CF) is a life-limiting autosomal recessive disorder affecting a large number of individuals in Europe. The disease arises from mutations in the CFTR gene encoding the cystic fibrosis transmembrane conductance regulator, a chloride ion channel crucial for maintaining epithelial ion and fluid homeostasis. Dysfunctional CFTR disrupts mucociliary clearance, particularly in the respiratory tract, resulting in persistent bacterial colonization, chronic inflammation, and progressive pulmonary damage—ultimately leading to respiratory failure, the principal cause of mortality in CF patients. Early diagnosis and advances in therapy have substantially improved both survival and quality of life. A hallmark of CF pathology is the establishment of polymicrobial infections within the thickened airway mucus. Pseudomonas aeruginosa is the dominant pathogen in chronic CF lung infections and demonstrates a remarkable capacity for adaptation via biofilm formation, metabolic reprogramming, and immune evasion. Biofilms confer increased tolerance to antimicrobial agents and facilitate long-term persistence in hypoxic, nutrient-limited microenvironments. P. aeruginosa exhibits a wide range of virulence factors, including exotoxins (e.g., ExoU, ExoS), pigments (pyoverdine, pyochelin), and motility structures (flagella and pili), which contribute to tissue invasion, immune modulation, and host damage. During chronic colonization, P. aeruginosa undergoes significant genotypic and phenotypic changes, such as mucoid conversion, downregulation of acute virulence pathways, and emergence of hypermutator phenotypes that facilitate rapid adaptation. Persistent cells, a specialized subpopulation characterized by metabolic dormancy and antibiotic tolerance, further complicate eradication efforts. The dynamic interplay between host environment and microbial evolution underlies the heterogeneity of CF lung infections and presents significant challenges for treatment. Elucidating the molecular mechanisms driving persistence, hypermutability, and biofilm resilience is critical for the development of effective therapeutic strategies targeting chronic P. aeruginosa infections in CF.